Seguridad en la administración de medicamentos en el Hospital General Isidro Ayora 2016-2017. - Lapo Camisan, Angel Duval (2017)
The research "SECURITY IN THE ADMINISTRATION OF MEDICINES IN THE GENERAL ISIDRO AYORA HOSPITAL 2016-2017" aims to determine, the application of safety measures in the administration of drugs in the Isidro Ayora Hospital in the city of Loja. The type of study to determine the application of safety measures in the administration of drugs in nursing professionals working at the Isidro Ayora Hospital in the city of Loja was descriptive. The sample consisted of 100 nursing professionals working at the Isidro Ayora Hospital in the city of Loja, to whom the survey was based on safety in the preparation and administration of medicines to the patient. As far as to the preparation of medication, 75% of nursing professionals sometimes perform disinfection of the work table; in the use of protective barriers, 75% don’t wear gloves and 85% don’t wear a mask. During medication administration, 85% perform a single hand wash to administer the medication to several patients; the correct 10 are applied 68% and 32% don’t effectively. It is determined that the majority of the nursing professionals in the General Isidro Ayora Hospital in the city of Loja, comply with the procedures required for the safety in preparation and administration of medicines, finding in minimum percentages that the professionals don’t disinfect the table work before starting the preparation; They don’t use protection barriers; Don’t verify the physical characteristics and expiration of the medicines as well as in the washing of hands and the optimal application of the ten correct ones. KEYWORDS: Routes of administration, biosecurity, medications, Isidro Ayora Hospital, disinfection.